About the applicability of flat systems theory in analysis and control of nonlinear systems - Phước, Nguyễn Doãn (Journal of Computer Science and Cybernetics, 2013)
Theory of flat systems has provided many opportunities, but not few challenges for solving of analysis and control problems. This article focuses on appreciations of these opportunities and from this ahead on some open theory problems to be carried out. With these appreciations, the paper provides also an objective view of applicability of flat systems theory in analysis and control of nonlinear systems.